Developing A Construction Model at Private Islamic Senior High School - Adripen Adripen; David David; Cut Afrina (AL-ISHLAH: Jurnal Pendidikan, 2022)
This research aimed to develop and validate the construction private Islamic high school model. This research method is research and development, Borg Gall model. The sample of 40 people consisted of foundation administrators, principals, vice-principals, and senior teachers. The assessment of the model was requested by the model users with a total of 20 people consisting of the principal and the head of the foundation. The study's data collections are through questionnaires, interviews, observations, and Delphi. The product to be developed is focused on management functions. Test the validity of the instrument using confirmation factor analysis. Based on the trial results, it had known the instrument used was valid and reliable. Analysis of the assessment results using Aiken found that the lowest V index was 0.625 and the highest was 0.775 with a rate of 20 people, and the rating category of 5 was obtained Vt = 0.64 with p = 0.05. Thus the entire Vo ≥ Vt, except in item 10 with a value of 0.625, but this number can be categorized quite well. It can be concluded that the Model of Private Islamic senior high schools Development in Tanah Datar is generally said to be valid. Based on the fittest the model was found (1) Chi-Square 386.07 2 x df (804), (2) P-Value 0.7074 0.05, (3) RMSEA 0.000 0.05, (4) GFI 0.97 0.90, and (5) Adjusted Goodness of Fit Index 0.970.90. Therefore, the model can be attached to fit.